Integrated qPCR and Staining Methods for Detection and Quantification of Enterocytozoon hepatopenaei in Shrimp Litopenaeus vannamei - Wang, Lijun (Microorganisms, 2020)
Enterocytozoon hepatopenaei (EHP) is an obligate, intracellular, spore-forming parasite, which mainly infects the gastrointestinal tract of shrimp. It significantly hinders the growth of shrimp, which causes substantial economic losses in farming. In this study, we established and optimized a SYBR Green I fluorescent quantitative PCR (qPCR) assay based on the polar tube protein 2 (PTP2) gene for the quantitative analysis of EHP-infected shrimp. The result showed that the optimum annealing temperature was 60 °C for the corresponding relation between the amplification quantitative (Cq) and the logarithmic of the initial template quantity (x), conformed to Cq = −3.2751x + 31.269 with a correlation coefficient R(2) = 0.993. The amplification efficiency was 102%. This qPCR method also showed high sensitivity, specificity, and repeatability. Moreover, a microscopy method was developed to observe and count EHP spores in hepatopancreas tissue of EHP-infected shrimp using Fluorescent Brightener 28 staining. By comparing the PTP2-qPCR and microscopy method, the microscopic examination was easier to operate whereas PTP2-qPCR was more sensitive for analysis. And we found that there was a correspondence between the results of these two methods. In summary, the PTP2-qPCR method integrated microscopy could serve for EHP detection during the whole period of shrimp farming and satisfy different requirements for detecting EHP in shrimp farming.